Prisonnier de Mao : sept ans dans un camp de travail en Chine - Pasqualini, Jean; Chelminski, Rudolph (Paris : Gallimard, 1976)
Bibliotheek François Vercammen
Frans
Meerdelige publicatie
Keywords: maoïsme